ANALISIS STRUKTURAL FABEL TEGODEK DAIT TETUNTEL: REPRESENTASI PERILAKU DALAM MASYARAKAT SASAK - Syaiful Bahri (Balai Bahasa Nusa Tenggara Barat, 2014)
This study analyzed structure of Tegodek Dait Tetuntel fable. Through these structures, it will be seen the role of each character in relationto the behavior of Sasak community based on the social levels . By using the structural analysis methods of Levi-Strau,it is shown that Tegodek and Tetuntel fable is not only presenting two main characters, ‘Godek’ (monkey) and Tuntel (frogs/toads), but it is also presenting some phenomena of opposition figures such as ‘Godek’ is always insuperior position, while figures of Tuntel is always in inferior position. This indicates that ‘Godek’ figure is representation of a higher social class, while Tuntel is representation of a lower social class. Relating to the behavior, the ‘Godek’ character has a more active behavior, while the Tuntel figure tends to bea passive behavior. If it is related to